PERBEDAAN KUALITAS HIDUP PASIEN USIA LANJUT SEBELUM DAN SETELAH OPERASI KATARAK - Adelia Lisnawati (UNUSA Press, 2020)
Cataract is a condition when the lens become cloudy and often occurs in elderly patients. Cataract is the leading cause of visual impairment and blindness in the world. Cataract can reduce productivity and social life, that will decrease the quality of life in elderly patients. It also reduces the visual acuity leading to decreasing visual function and the quality of life. This disease can change physical, cognitive and psychosocial life. This study aimed to analyze the difference of quality of life in elderly patients before and after cataract surgery at SMEC eye clinic in Samarinda. This study was observational analytic study. Data were taken from interview the patients with visual function questionnaire 14 (VFQ 14) and from the medical record of SMEC eye clinic in Samarinda. The results showed a significant difference of quality of life in elderly patients before and after cataract surgery (p = 0,000) with the mean score of quality of life before surgery (x̅= 63,65) was lower than after cataract surgery (x̅= 95,35) and there was significant improvement of the visual acuity after cataract surgery (p = 0,000). Based on these results it can be concluded that there were difference of quality of life in elderly patients before and after cataract surgery.